Mahārah Kalām Book: The Implementation at Arabic Course - Nur Cholifah; Frida Akmalia (ALSUNIYAT, 2021)
In this study, the researchers focus on implementing mahārah kalām book at Al-Azhar Arabic course, Pare. This study used a descriptive qualitative approach. The data were collected using observation, interviews, and documentation. Miles and Huberman techniques were used to analyzing the data. The results reveal that: first, the textbooks used are books compiled directly by the founder of the course. There are al-muhādaṡah 1, mufradāt 1500 vocabularies, and al-qawāid al-taysīr. Second, in the learning process, the teacher used various methods, namely conversation, singing, question answering, and memorization. Third, the daily evaluation of speaking skills is in the form of a test that requires the students to make a story, which should be memorized and then practiced in front of the class. Finally, the final evaluation covers all the materials learned within 5 -10 minutes.